2022
DOI: 10.32604/iasc.2022.025485
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Data Hiding in Encrypted Images Based on Adaptive Prediction-error Label Map

Abstract: In the field of reversible data hiding in encrypted images (RDH-EI), predict an image effectively and embed a message into the image with lower distortion are two crucial aspects. However, due to the linear regression prediction being sensitive to outliers, it is a challenge to improve the accuracy of predictions. To address this problem, this paper proposes an RDH-EI scheme based on adaptive prediction-error label map. In the prediction stage, an adaptive threshold estimation algorithm based on local complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This method has better robustness and security performance, resisting most image attacks. Ren et al [19] proposed an RDH-EI scheme based on an adaptive prediction-error label map. Extensive experimental results have shown that the proposed method can achieve effective pixel prediction results and obtain a higher embedding rate (ER).…”
Section: Related Workmentioning
confidence: 99%
“…This method has better robustness and security performance, resisting most image attacks. Ren et al [19] proposed an RDH-EI scheme based on an adaptive prediction-error label map. Extensive experimental results have shown that the proposed method can achieve effective pixel prediction results and obtain a higher embedding rate (ER).…”
Section: Related Workmentioning
confidence: 99%